The effect a counseling and psychotherapy program from an Islamic perspective on reducing anxiety and achieving mental health among the students female of Irbid University College - Al-Hamad, Nayef (Jordan Journal of Islamic Studies, 2023)
The study aimed to know the effect of a therapeutic counseling program in reducing anxiety and achieving mental health among university students female, And the study sample consisted of (14) students female from Irbid University College - Al Balqa Applied University, They were intentionally chosen as those who had high Degrees on the anxiety scale and low Degrees on the mental health scale. And they were distributed to two equal groups, an experimental group consisting of (7) students female, And a control group consisted of (7) students female, were used The psychological anxiety scale, the mental health scale, and the Islamic counseling and therapy program, While the control group did not experience the counseling program. And the study found in its results that there are statistically significant differences between the scores of the experimental group students and the scores of the control group students on the anxiety scale and on the mental health scale after implementing the counseling program, And for the benefit of the post evaluation; that is, Efficacy The counseling and Islamic therapy program to reduce anxiety and achieve mental health among students female In the experimental group, One of the most important recommendations of the study is to generalize the use of the field of Islamic counseling and therapy as it one of the fields of counseling and psychotherapy that is effective in bringing about a direct change in personality and treatment of mental health.